2020
DOI: 10.1111/jfpe.13527
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the efficiency of two modeling approaches for predicting moisture content of apple slice during drying

Abstract: The efficiency of two different modeling approaches for predicting moisture content of apple slices during drying were evaluated and compared. The experiments were performed at four air‐drying temperatures and at three levels of air velocity in the convective hot air dryer. Moisture content of apple during drying was predicted using theoretical model and Artificial Neural Networks (ANNs) models. The theoretical model was developed by solving heat and mass transfer equations simultaneously using numerical techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The average error of the BP‐ANN model in predicting the moisture content of rice was 0.2, and the model prediction performance was superior. The results of this paper were similar to those reported in the literature by other researchers, and the artificial neural network fits well with the data obtained from the experimental data (Dalvi‐Isfahan, 2020; Tavakolipour & Mokhtarian, 2012). In addition, similar results were obtained for vacuum drying, spray drying and superheated steam drying, demonstrating the strong adaptability and good simulation performance of artificial neural networks (Chai et al, 2018; Li et al, 2021; Shrivastav & Kumbhar, 2011).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The average error of the BP‐ANN model in predicting the moisture content of rice was 0.2, and the model prediction performance was superior. The results of this paper were similar to those reported in the literature by other researchers, and the artificial neural network fits well with the data obtained from the experimental data (Dalvi‐Isfahan, 2020; Tavakolipour & Mokhtarian, 2012). In addition, similar results were obtained for vacuum drying, spray drying and superheated steam drying, demonstrating the strong adaptability and good simulation performance of artificial neural networks (Chai et al, 2018; Li et al, 2021; Shrivastav & Kumbhar, 2011).…”
Section: Resultssupporting
confidence: 90%
“…The empirical models are developed by fitting model parameters to experimental data, based on the relationship between moisture content and drying time. Mathematical modeling methods are subject to limitations in the application, such as the choice of parameters, computing time, the application of assumptions in solving equations and the complexity of solving equations (Dalvi‐Isfahan, 2020). In addition, the moisture content of the materials is significantly nonlinear and time‐varying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of neurons in the hidden layer, thresholding function and training algorithm are the famous factors that need to be adjusted to construct the model. For determining the number of neuron in the hidden layer, trial and error method was used and based on previous researches the tansig and linear function were used as transfer function in the hidden and output layers, respectively, Levenberg–Marquardt (LM) back‐propagation algorithm with the early stopping method was used for training of the ANN model (Dalvi‐Isfahan, 2020; Khaled et al, 2020). The performance assessment of ANN models was evaluated by the root mean square error (RMSE) and correlation coefficient ( R ) between the predicted values by model and the target data.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the newest comprehensive discussions about the capability and robustness of ANN for modeling the drying process were done by Khan, Sablani, Joardder, and Karim (2020) and Chen et al (2020). Also, Khaled et al (2020); Dalvi‐Isfahan (2020) and Abbaspour‐Gilandeh, Jahanbakhshi, and Kaveh (2019) results indicated that the ANN had a good strength for dynamic modeling of moisture content during the drying process. Also, Liu et al (2020) applied the ANN benefit for optimizing the drying process in the vacuum dryer.…”
Section: Introductionmentioning
confidence: 96%